Influence of Silicon Dioxide-Titanium Dioxide Antireflective Electrosprayed Coatings on Multicrystalline Silicon Cells. (8th October 2022) - Rathanasamy, Rajasekar; Velu Kaliyannan, Gobinath; Sivaraj, Santhosh; Saminathan, Abishek; Krishnan, Bharathikannan; Palanichamy, Dhayananth; Uddin, Md. Elias
Abstract : This research work primarily focuses on enhancing the power conversion efficiency (PCE) of polycrystalline silicon solar cells by using a single-layer and a double-layered antireflection coating deposited through the electrospraying technique. The usage of titanium dioxide and silicon dioxide as antireflection coating materials has shown a significant increase in the optical and electrical properties of solar cells under open and controlled light sources. The sample with TiO2 as a base layer and SiO2 as the top layer (sample B-IV) exhibited a maximum PCE of 18.90% in direct sunlight and 21.19% in a neodymium setup with cell temperatures of 40°C and 52.1°C, respectively. Sample B-IV has also shown the lowest resistivity of 3.1 × 10 −3  Ω·cm among the coated samples. Also, an increase of 11.6% light transmittance and a reduction of 9.6% light reflectance were exerted by sample B-IV. The results obtained from different analysis proves that TiO2 /SiO2 was an appropriate antireflection coating material for enhancing the PCE of the polycrystalline silicon solar cell.